Analysis of the Application of Target Costing in Managing Production Costs to Increase Profits in the Solo Medan Sausage SME - Nurul Isnaini Putri; Nur Ahmadi Bi Rahmani; Yenni Samri Juliati Nasution (Jurnal Manajemen Bisnis, 2024)
The implementation of target costing by an UMKM trader aims to reduce total costs from the previous total costs so that the company can get maximum profits without having to increase its selling price. This research aims to analyze whether the application of the Target Costing method in managing production costs at Solo Medan Sosis UMKM can optimize profits as expected. This research was conducted using a qualitative and descriptive approach method and was carried out in the city of Medan starting in December 2023. The results of this research show that by using the Target Costing method the required production costs can be minimized so that the profits obtained can be further optimized in accordance with the company's expectations. without increasing product prices. So the conclusion is that the Target Costing method can be an alternative for Solo Medan Sosis UMKM in determining production cost.